2017
DOI: 10.3174/ajnr.a5265
|View full text |Cite
|
Sign up to set email alerts
|

The Initial Area Under the Curve Derived from Dynamic Contrast-Enhanced MRI Improves Prognosis Prediction in Glioblastoma with UnmethylatedMGMTPromoter

Abstract: IAUC can be a useful prognostic imaging biomarker in patients with glioblastoma with known status, improving prediction of glioblastoma prognosis with the unmethylated promoter status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…87 The same group also reported that the initial area under the time-to-signal intensity curve from DCE imaging stratifies survival in promoter unmethylated MGMT GBM, but not in methylated tumors. 89 Arecent study combined both structural and physiologic MR imaging to derive an accurate marker for MGMT promoter methylation status in 92 patients with GBM. The authors found that MGMT promoter methylation was associated with increased ADC and decreased rCBF(from ASL imaging).…”
Section: Clinical Applications Of Advanced Mrimentioning
confidence: 99%
“…87 The same group also reported that the initial area under the time-to-signal intensity curve from DCE imaging stratifies survival in promoter unmethylated MGMT GBM, but not in methylated tumors. 89 Arecent study combined both structural and physiologic MR imaging to derive an accurate marker for MGMT promoter methylation status in 92 patients with GBM. The authors found that MGMT promoter methylation was associated with increased ADC and decreased rCBF(from ASL imaging).…”
Section: Clinical Applications Of Advanced Mrimentioning
confidence: 99%
“…25 One study was prospective in design. 26 Twenty studies were retrospective, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]27,28,[30][31][32] and 1 study did not explicitly state the design. 29 Study enrollment was consecutive in 3 studies 16,18,25 and not explicit in the remaining studies.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…26 Twenty studies were retrospective, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]27,28,[30][31][32] and 1 study did not explicitly state the design. 29 Study enrollment was consecutive in 3 studies 16,18,25 and not explicit in the remaining studies. Fifteen of 22 studies used methylation-specific polymerase chain reaction as a reference standard to detect MGMT methylation, 11,[14][15][16][19][20][21][22][23][24]27,28,[30][31][32] with the other studies using DNA methylation analysis, 18 pyrosequencing, 13 immunohistochemical staining, 29 or multiplex ligation-dependent probe amplification, 26 with the method not being stated in 3 studies.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations